Returning individual wearable sensor results to participants: perspectives on challenges and lessons learned - Leonard-Corzo, Krista S.; Bachman, Shelby L.; Blankenship, Jennifer M.; Clay, Ieuan; Lyden, Kate (Frontiers in Digital Health, 2025)
With increased adoption of digital health technologies in clinical trials, sponsors and investigators are often faced with the challenge of promoting participant compliance and engagement. One strategy that may provide value to participants and, as such, help improve compliance with digital health technologies is to return individual study results to participants. Clinical research participants have consistently expressed their desire to receive individual study results following participation in a trial, and trial sponsors and investigators are eager to comply. However, multiple challenges and barriers to its implementation mean that return of results is rarely carried out, despite alignment around its value. This perspective discusses the potential benefits of returning individual study results, including improved participant engagement and compliance, increased patient trust, and increased sense of health ownership. We also discuss the practical challenges of and barriers to returning individual study results from digital health technologies back to participants related to what, how, and when to return results. We assert that clinical trial sponsors and investigators should consider returning individual study results to participants and propose potential solutions to address specific challenges.